2009
DOI: 10.1002/anie.200803347
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Biological Properties of Aspirin by Formation of a Bioorganometallic Derivative

Abstract: Beyond treating headaches: The derivatization of biologically active compounds by organometallic units modulates their pharmacological properties. In studies of antitumor‐related biochemical properties, the Co2(CO)6 derivative of aspirin 1 shows significantly modified influence on several relevant pathways, which might be based on an altered interaction with the target enzyme COX‐2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
94
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(98 citation statements)
references
References 30 publications
1
94
0
3
Order By: Relevance
“…30 However, Ott et al showed that cobalt-aspirin complex leaves the serine residue untouched and acetylates other sites instead that may result in a different activity spectrum for the drug. 31 In summary, our data demonstrate the superiority of zinc complex of ASA to ASA in preventing postischemic myocardial dysfunction. Induction of anti-oxidant enzymes and the anti-inflammatory cytokine TGF-b 1 may play a pivotal role in the mechanism of action of Zn(ASA) 2 .…”
mentioning
confidence: 52%
“…30 However, Ott et al showed that cobalt-aspirin complex leaves the serine residue untouched and acetylates other sites instead that may result in a different activity spectrum for the drug. 31 In summary, our data demonstrate the superiority of zinc complex of ASA to ASA in preventing postischemic myocardial dysfunction. Induction of anti-oxidant enzymes and the anti-inflammatory cytokine TGF-b 1 may play a pivotal role in the mechanism of action of Zn(ASA) 2 .…”
mentioning
confidence: 52%
“…A new approach involves modelling the pharmacological properties of established drugs with organometallic fragments (Ott et al, 2009). The metallocyclic peptide, bacitracin, has an interesting SOD activity.…”
Section: Fig 2 Structures Of Carboplatin (Left) and Oxaliplatin (Rimentioning
confidence: 99%
“…Cobalt-aspirin complexes are investigated as potential cytostatics (Ott et al, 2009). Aspirin (acetylsalicylic acid) belongs to the family of nonsteroidal antirheumatics (NSAR), which have anti-inflammatory and pain-relieving effects The pharmacological effects of NSARs stem from the inhibition of enzymes in the cyclooxygenase family (COX).…”
Section: Fig 2 Structures Of Carboplatin (Left) and Oxaliplatin (Rimentioning
confidence: 99%
See 1 more Smart Citation
“…Encouragingly, some metal-NSAID complexes exhibit greater cytotoxicity than cisplatin. A recent comprehensive review It should be noted that several metal-NSAIDs have been previously reported, and their binding to biomolecules such as DNA and human serum albumin (HSA) has been well characterized using spectroscopic methods [48][49][50][51][52]. In general, metal-NSAID complexes display stronger binding to biomolecules than the corresponding free NSAID.…”
Section: Introductionmentioning
confidence: 99%